EDUCATION, HEALTH, AND PUBLIC SERVICE IN INDONESIA: AN ISLAMIC ECONOMICS VIEW - Noor Muhariah Dorojatun (Universitas Airlangga, 2018)
The main object in this paper are two. First, to determine the suitability of laws on education and health to the government expenditure of Indonesia in Islamic economics view. Second, to devise guidelines for national policymakers in the implementation of government expenditure in education and health which gives utmost priority to public service. The distinctive feature of this paper is not only to see the increasing government expenditure and public services but in additional to implement the maximum government expenditure in education and health, there needs to be a minimum standard service which we see not only from the laws but from Islamic economics too. This paper contains as follow: section 1 commences with the sneak peak of Islamic economics, the increasing of government expenditure phenomenon, and empirical study about health and education. Section 2 addresses the state expenditure in Islam, the definition of government expenditure according to law, quality of services in Islam, and the definition of public services. Section 3 discusses education and health expenditure according to law and the minimum service standard for both and last, Section 4 is the conclusion.